Mesoporous crystalline Ti1-xSnxO2 (0 < x < 1) solid solution for a high-performance photocatalyst under visible light irradiation - Yu, Wen; Geng, Nankun; Han, Jianming; Yu, Wenjun; Peng, Yiting (Frontiers in Chemistry, 2022)
We report a facile and effective inorganic polycondensation combined with aerosol-spray strategy towards high-performance photocatalyst by fabricating mesoporous Ti1-xSnxO2 (0 < x < 1) solid solution. Such Ti1-xSnxO2 nanocrystals with high Sn-doped contents are self-assembled into mesoporous spheres can effectively promote visible-light harvest and high quantum yield, leading a longer lifetime of the photoelectron-hole pairs and less recombination. Such the photocatalysts enhanced photocatalytic activity for the degradation of Rhodamine B (RhB). The representative Ti0.9Sn0.1O2 and Ti0.8Sn0.2O2 compounds reach an optimum degradation of ≈ 50% and 70%, respectively, after 120 min irradiation under visible irradiation. The mesoporous Ti1-xSnxO2 solid solution could inhibit the recombination of electron-hole pairs, which promote reaction thermodynamics and kinetics for RhB degradation.